Sicilian Futures in the Making: Living Species and the Latency of Biological and Environmental Threats. Issue 1 (1st March 2019) - Benadusi, Mara
Abstract : Discourses and practices of anticipation occupy a hypertrophic space in contexts where uncontrolled industrial growth has inflicted grave damage on peoples and territories, even triggering environmental disasters. This article explores the use of nonhuman species as anticipatory devices in a petrochemical terminal in Sicily, focusing on public representations of three species: scavenger bacteria that play a cleansing role and underline citizens' moral responsibility to secure their best possible futures through bioscience; migrating flamingos that breed under the petrochemical chimneys, raising the possibility of hopefulness by highlighting ecosystem resilience; and fish affected by spina bifida, which reveal human health status in advance, communicating the need to live in preparation for potential diseases. The analysis reveals the highly contentious character of these anticipatory devices and the contested ideas about possible futures they imply, thus shedding light on the ecological frictions that have repercussions locally and globally, in discourse and social practice.